Green measures for Markov processes - Kondratiev, Yu. G.; Silva, J. L. (Methods of Functional Analysis and Topology, 2020)
In this paper we study Green measures of certain classes of Markov processes. In particular Brownian motion and processes with jump generators with different tails. The Green measures are represented as a sum of a singular and a regular part given in terms of the jump generator. The main technical question is to find a bound for the regular part. Ми вивчаємо міри Ґріна для деяких класів марківських процесів. Зокрема для броунівського руху і стрибкових процесів. Міри Ґріна містять сингулярну і регулярну компоненти. Основна задача полягає в оцінці регулярної частини.